Taxonomy of Educational Goals and Evaluation of Learning Outcomes - Siddik, Ananda; Fadillah, Akbar Al; Sitepu, Egianisa Br; Ihsan, Farraz Aulia; Ratih, Indah Sri (Lembaga Riset Mutiara Akbar, 2025)
This research aims to explore the implementation of a taxonomy of educational objectives in the assessment of learning to occur in order to improve the quality of the learning process. The approach used is a qualitative method, using data collection through literature study, document analysis, and in-depth interviews with educators from various levels of education. The analytical framework used refers to Bloom's updated taxonomy, covering cognitive, affective and psychomotor domains. The research results show that there is an emphasis on mastery of low-level cognitive domains, such as remembering and understanding, while the development of high-level abilities, such as analyzing, evaluating and creating, does not receive adequate attention. Apart from that, the affective and psychomotor domains tend to be neglected in the learning planning process, even though these domains play a crucial role in supporting the formation of students' character and practical skills. This research concludes that implementing a balanced taxonomy of educational objectives can strengthen the relevance and effectiveness of learning, and recommends improving educator training in setting objectives and evaluating learning outcomes more comprehensively.